Early Cretaceous origin of pollen‐feeding beetles (Insecta: Coleoptera: Oedemeridae). (23rd June 2016) - Peris, David
Abstract: The taxonomic position of a new pollen‐feeding fossil beetle from Spanish amber (late Albian, 105 Ma) is analysed. A phylogenetic analysis allows me to accommodate Darwinylus marcosi gen. et sp. nov. in the Polyphaga: Oedemeridae within current limits for the family, which clearly belongs in the subfamily Oedemerinae. It corresponds to the oldest definitive record for the family. Some autapomorphies, mainly in antennae, are observable in the fossil compared with extant members of the family. A discussion about these problematic characters and the evolution of the family is proposed.